Comparison of the lethal triad and the lethal diamond in severe trauma patients: a multicenter cohort - Charles Dupuy; Thibault Martinez; Olivier Duranteau; Tobias Gauss; Natacha Kapandji; Jean Pasqueron; Mathilde Holleville; Georges Abi Abdallah; Anatole Harrois; Véronique Ramonda; Delphine Huet-Garrigue; Théophane Doublet; et al. (World Journal of Emergency Surgery)
Abstract Background To reduce the number of deaths caused by exsanguination, the initial management of severe trauma aims to prevent, if not limit, the lethal triad, which consists of acidosis, coagulopathy, and hypothermia. Recently, several studies have suggested adding hypocalcemia to the lethal triad to form the lethal diamond, but the evidence supporting this change is limited. Therefore, the aim of this study was to compare the lethal triad and lethal diamond for their respective associations with 24-h mortality in severe trauma patients receiving transfusion. Methods We performed a multicenter retrospective analysis of patients in TraumaBase®, a French database (2011–2023). The patients included in this study were all trauma patients who had received transfusions of at least 1 unit of red blood cells (RBCs) within the first 6 h of hospital admission and for whom ionized calcium measurements were available. Hypocalcemia was defined as an ionized calcium level < 1.1 mmol/L. Results A total of 2141 severe trauma patients were included (median age: 39, interquartile range [IQR]: 26–57; median injury severity score: 27, IQR: 17–41). Patients primarily presented with blunt trauma (81.7%), and a 24-h mortality rate of 16.1% was observed. Receiver operating characteristic curve analysis revealed no significant difference in the association with 24-h mortality between the lethal diamond (area under the curve [AUC]: 0.71) and the lethal triad (AUC: 0.72) (p = 0.26). The strength of the association with 24-h mortality was similar between the lethal triad and the lethal diamond, with Cramer’s V values of 0.29 and 0.28, respectively. Conclusions This study revealed no significant difference between the lethal triad and the lethal diamond in terms of their respective associations with 24-h mortality in severe trauma patients requiring transfusion. These results raise questions about the independent role of hypocalcemia in early mortality.